Research and experiment of electrostatic spraying system for agricultural plant protection unmanned vehicle - Lin, Zhen; Xie, Jinye; Tian, Shuo; Wang, Xihong; Sun, Wenfu; Mo, Xiaoqin (Frontiers in Ecology and Evolution, 2023)
The traditional spraying system is not suitable for agricultural plant protection in small plots due to its disadvantages of weak droplet refining ability, small spraying area, large pesticide consumption and high manual spraying cost. At present, spraying pesticide is the main way to resist crop diseases and insect pests. The utilization rate of pesticide is only 38.8% in China, which leads to serious waste and serious environmental pollution. It is necessary to develop advanced plant protection equipment and pesticide application technology to solve the problem. The combination of agricultural plant protection vehicle and electrostatic spray technology may solve the problems of spraying efficiency, droplet adsorption rate and evenness. It is of great significance to improve the efficiency of plant protection and pesticide utilization. In this paper, the principle of droplet charging is described, an electrostatic spraying system is designed and tested, and the effects of charging voltage and pump pressure on the droplet charge ratio and droplet size are analyzed. This study has shown that electrostatic spraying systems are suitable for agricultural plant protection unmanned vehicles.